A model for managing the security of maritime critical infrastructure under the conditions of the fourth industrial revolution = Model zarządzania bezpieczeństwem morskiej infrastruktury krytycznej w warunkach czwartej rewolucji przemysłowej - Igielski, Michał (Zielona Góra: Faculty of Economics and Management Press)
The primary objective of the author of this paper is to propose a preliminary and theoretical model of security management of maritime critical infrastructure under the conditions of the fourth industrial revolution. The proposed model in the definition is to be comprehensive in terms of shaping information security management.
Keywords: fourth industrial revolution; critical infrastructure; security management; czwarta rewolucja przemysłowa; infrastruktura krytyczna; zarządzanie bezpieczeństwem